Analysis of Teacher Readiness, Science Process Skills (SPS), and Implementation of Process-Oriented Guided Inquiry Learning (POGIL) Model in Elementary Schools - Siti Aisah; Willa Putri; Safrizal (Universitas Negeri Medan, 2026)
Low scientific literacy among Indonesian primary school students highlights an urgent need for instructional transformation. While previous research separate these elements, this study addresses a significant empirical gap by simultaneously examining multidimensional teacher readiness, conceptual knowledge of scientific process skills, and the actual implementation of the process-oriented guided inquiry learning model at the primary education level. Using a quantitative descriptive and correlational design, data were collected via questionnaires and tests from 121 primary school science teachers across 14 sub-districts in Bogor Regency. The results showed that while average teacher readiness reached the good category, teachers' conceptual mastery of scientific process skills remained deficient, with over 33% scoring in the low and very low categories. Regression analysis revealed that teacher readiness contributes a positive but low 7.1% to their skills knowledge, whereas teaching experience yields no significant impact. Furthermore, model implementation drops drastically from 73.6% at the initial orientation stage to only 17.4% during the core application phase. The primary barriers preventing full implementation are limited science learning media and a lack of practical hands-on training for process-oriented instruction. This study concludes that high affective and behavioral readiness does not automatically guarantee conceptual mastery of scientific inquiry. Consequently, content-specific inquiry skills must be treated as a distinct, mandatory dimension within teacher readiness frameworks, supported by strategic institutional allocation of concrete instructional aids and targeted professional workshops.